« C’est bien la loi d’un pays à forte émigration » Principes de la nationalité et représentations de la nation au Liban - Thibaut Jaulin (Revue des Mondes Musulmans et de la Méditerranée)
This paper questions the relationship between the representation of Lebanon as an emigration country and the supremacy of the right of blood in the Lebanese nationality law, at the expense of the right of soil. By doing so, it intends to understand the relation between citizenship, defined as a factor of inclusion and exclusion, and the invention of the Lebanese national identity. It adopts an approach based on the analysis of norms, rather than practices. In a first section, it shows how the representation of Lebanon as an emigration country justifies the supremacy of the right of blood in the legal literature of the French mandate in Lebanon. Then, through the writings of two political thinkers (Antoun Saade and Michel Chiha), it analyzes how the emigrant has become a key figure of the (Lebanese and Pan-Syrian) national imaginary, and an object of competing representation, in relation with antagonist conceptions of the nation.